2018
DOI: 10.1200/jco.2017.75.2998
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cell Number as a Response Measure of Prolonged Survival for Metastatic Castration-Resistant Prostate Cancer: A Comparison With Prostate-Specific Antigen Across Five Randomized Phase III Clinical Trials

Abstract: Measures of response that are clinically meaningful and occur early are an unmet need in metastatic castration-resistant prostate cancer clinical research and practice. We explored, using individual patient data, week 13 circulating tumor cell (CTC) and prostate-specific antigen (PSA) response end points in five prospective randomized phase III trials that enrolled a total of 6,081 patients-COU-AA-301, AFFIRM, ELM-PC-5, ELM-PC-4, and COMET-1-ClinicalTrials.Gov identifiers: NCT00638690, NCT00974311, NCT01193257… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
143
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 18 publications
10
143
1
Order By: Relevance
“…The enriched cell suspension was fluorescently labeled with the PE-labeled CAM5.2 antibody recognizing cytokeratins 7 and 8, a PerCP-labeled antibody recognizing CD45 and a nucleic acid dye that could be measured in the FITC channel of a flowcytometer. By now the original results have been confirmed and validated in numerous studies and expanded to different cancers and earlier disease stages (15)(16)(17)(18)(19)(20). These results were sufficiently encouraging to further develop the CTC technology and design and conduct clinical studies to explore the clinical utility of CTC.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The enriched cell suspension was fluorescently labeled with the PE-labeled CAM5.2 antibody recognizing cytokeratins 7 and 8, a PerCP-labeled antibody recognizing CD45 and a nucleic acid dye that could be measured in the FITC channel of a flowcytometer. By now the original results have been confirmed and validated in numerous studies and expanded to different cancers and earlier disease stages (15)(16)(17)(18)(19)(20). These results were sufficiently encouraging to further develop the CTC technology and design and conduct clinical studies to explore the clinical utility of CTC.…”
mentioning
confidence: 69%
“…The real excitement arose when the results of the prospective studies became available which showed that CTC were superior to serum tumor markers and/or radiographic imaging in predicting efficacy of ongoing therapy (10)(11)(12)(13)(14). By now the original results have been confirmed and validated in numerous studies and expanded to different cancers and earlier disease stages (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Most metastatic prostate cancers spread through the blood as circulating tumor cells (CTCs), and enumeration of CTCs correlates with baseline and postbaseline prognosis in the mCRPC population . PSMA expression on circulating tumor cells is emerging as a potential method of measuring treatment response .…”
Section: Introductionmentioning
confidence: 99%
“…10 Most metastatic prostate cancers spread through the blood as circulating tumor cells (CTCs), and enumeration of CTCs correlates with baseline and postbaseline prognosis in the mCRPC population. 11 PSMA expression on circulating tumor cells is emerging as a potential method of measuring treatment response. 12 PSMA and PSA biomarkers are being used to identify circulating PCa cells in blood, 13,14 and high concordance with results of FDA-cleared CellSearch assays have been demonstrated in studies using realtime quantitative reverse-transcription polymerase chain reaction (RT-PCR) methods for messenger RNA (mRNA) detection and quantification.…”
Section: Introductionmentioning
confidence: 99%
“…3 While there is obvious heterogeneity among CTCs, CTCs can be defined as epithelial type (eCTC), mesenchymal type (mCTC), biophenotypic type (bCTC), and CTCs mass (CTM) according to different expression patterns of epithelial and mesenchymal markers of CTCs. [5][6][7] Wu et al 8 reported that changes in gene expression in CTCs can affect the prognosis of CRC, such as the expression of mesenchymal markers. [5][6][7] Wu et al 8 reported that changes in gene expression in CTCs can affect the prognosis of CRC, such as the expression of mesenchymal markers.…”
Section: Introductionmentioning
confidence: 99%